2012
DOI: 10.1111/j.2042-7158.2011.01378.x
|View full text |Cite
|
Sign up to set email alerts
|

3′-O, 4′-O-aromatic acyl substituted 7,8-pyranocoumarins: a new class of P-glycoprotein modulators

Abstract: Results from the study suggested that 3'-O, 4'-O-aromatic acyl substituted 7,8-pyranocoumarins could serve as a new class of Pgp modulator. Acyls play an important role in maintaining and enhancing the Pgp-modulating ability of pyranocoumarins. 3,4-Dimethoxyl substituted aromatic acyls, bearing a methoxy that might interact with Pgp as hydrogen bond accepter, were shown to be the most potent for reversing MDR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Several dihydropyranocoumarins exhibited not only anti-tumor activities but also multi-drug resistance reversing activities by interacting with Pgp, which serves as an efflux pump for xenobiotic compounds such as anti-tumor drugs Ren et al, 2013;Shen et al, 2012;Wu et al, 2003). Shen et al showed that 3 0 ,4 0 -aromatic acyloxy-substituted 7,8-pyranocoumarins exhibit higher activity in modulating Pgp, and those with 3 0 ,4 0 -cis-configuration are more effective than their trans isomers (Shen et al, 2012). Some dihydropyranocoumarins reportedly exhibit anti-HIV activities, and the rigid stereochemistry of a 3 0 R,4 0 R-cis-configurations is necessary for these activities (Huang, Kashiwada, Cosentino, Fan, & Lee, 1994;Xie et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several dihydropyranocoumarins exhibited not only anti-tumor activities but also multi-drug resistance reversing activities by interacting with Pgp, which serves as an efflux pump for xenobiotic compounds such as anti-tumor drugs Ren et al, 2013;Shen et al, 2012;Wu et al, 2003). Shen et al showed that 3 0 ,4 0 -aromatic acyloxy-substituted 7,8-pyranocoumarins exhibit higher activity in modulating Pgp, and those with 3 0 ,4 0 -cis-configuration are more effective than their trans isomers (Shen et al, 2012). Some dihydropyranocoumarins reportedly exhibit anti-HIV activities, and the rigid stereochemistry of a 3 0 R,4 0 R-cis-configurations is necessary for these activities (Huang, Kashiwada, Cosentino, Fan, & Lee, 1994;Xie et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…3A). Dihydropyranocoumarins are notable because of their various activities, such as calcium antagonist (Kozawa, Sakai, Uchida, Okuyama, & Shibata, 1981), antiplatelet aggregation (Aida, Kasama, Takeuchi, & Tobinaga, 1995), and Pglycoprotein (Pgp) modulating activities (Shen et al, 2012). All coumarins used in this study are dihydropyranocoumarins; all have acyloxy groups in positions R 1 and R 2 and have similar chemical structures (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Natural khellactone coumarins have been mainly isolated from Peucedanum species 810. In the past 2 decades, khellactone and its derivatives have attracted great interest in medicinal chemistry owing to their wide range of biological effects including antiviral activity,11 inhibition of platelet aggregation,12 calcium antagonist activity,13 and inhibition of P-glycoprotein 14,15. In particular, attention has been focused primarily on their anti-HIV activity, and some khellactone derivatives have been found to demonstrate extremely potent inhibitory activity against HIV-1 replication 16,17.…”
Section: Introductionmentioning
confidence: 99%
“…More and more studies are finding the anti‐tumour utilization of PA and PB. For example, PA and its derivatives have been demonstrated to reverse P‐glycoprotein‐mediated multidrug resistance in cancer cells (Shen et al , ; Shen et al , ; Fong et al , ). Praeruptorin A and B have been reported to exhibit therapeutic function towards gastric cancer (Liang et al , ).…”
Section: Introductionmentioning
confidence: 99%